Strain localization via mechanical mixing and metasomatism: an example from the metagabbros of Marine de Giottani, Alpine Corsica, France - Cenki Bénédicte; Oliot Emilien; Gueydan Frédéric; Nègre Lucille; Padrón-Navarta José Alberto (BSGF - Earth Sciences Bulletin)
Alpine deformation in the meta-ophiolitic nappe of the Upper Oceanic Unit of Corsica occurs under greenschist facies conditions. It is notably characterized by a series of shear zones in metagabbros. These shear zones are centimetre- to decimetre-size and are composed of amphibole ± chlorite schists. This occurrence offers a unique opportunity to study mechanisms of low-grade shear zone formation, extensive fluid/rock interaction and weakening processes controlled by mineralogical changes in the metamorphosed oceanic crust in the shallow part of a subduction system. A detailed sampling of undeformed metagabbros, protomylonitic metagabbros, as well as mylonitic schists allows tackling several finite strain states that involved rare occurrence of serpentinite clasts within the fault zones. Petrological observations combined with thermodynamic and geochemical modelling indicate that the metagabbro to amphibole-chlorite schist transformation involved mass transfer and occurred under open-system and water-saturated conditions. The main chemical features of this metasomatic process are significant gains in MgO, H2O, SiO2 and Fe2O3 accompanied by an almost complete loss of Na2O. The transformation of metagabbros into schists occurs under water-saturated open-system conditions and is triggered by strain localization via mechanical mixing (with serpentinite clasts) and Mg-rich metasomatic fluids. Deciphering the softening processes controlled by the transformation of metagabbros into low-grade schistose rocks are of major importance to understand the seismogenic behavior of the mafic crust during subduction.